Kompasrasi Unjuk Kerja Aplikasi File Transfer Protocol dengan MPLS pada Jaringan IPv4 dan IPv6 - Aidha Putri, Evi Zulfa; Cobantoro, Adi Fajaryanto; Arifin, Rizal (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
The number of devices using the IPv4 protocol has greatly increased. The IPv4 protocol is out of date because it no longer has the ability to support so many devices. The development of IPv6 as a future protocol to replace IPv4 is still ongoing. With an address space of 128 bits, IPv6 increases the number of available IP addresses. This study describes a simulation of Multi Protocol Label Swicthing (MPLS) network performance in a comparison between IPv4 and IPv6. The parameters observed were QoS, including delay, throughput and transfer time. The results of the analysis carried out showed that network differences have different effects on the parameter values of delay, throughput and transfer time. On MPLS IPv6 networks, the delay is smaller than MPLS IPv4 networks. For throughput and transfer time, IPv6 is also superior to IPv4.